Relating motivational problems to motivation regulation strategies - Nob, Rene M. (Animo Repository, 2019)
Advancing research in motivation regulation requires an exploration of the predictive relationship between motivational problems experienced by individuals and the motivational regulation strategies they use. Furthermore, this study also examined the potential enhancing role of metamotivation on the supposed relationship. The current study examined these processes in the context of the experiences of reviewees for a Civil Engineering board examination. In order to do this, the qualitative phase looked into what motivational problems reviewees encounter. On the other hand, the quantitative phase explored relationships between problems and strategies and the moderating role of metamotivation in such. Findings reveal that reviewees mostly encounter motivational problems that have been identified in previous literature. However, context-dependent patterns about specific motivational problems also emerged. A six-component structure of motivational problems was identified. In general, the motivation regulation strategies used by reviewees seem to match the motivational problems they experience. However, it seems that the match is not a simple one-to-one correspondence. Concrete motivation problems predicted the use of concrete motivational regulation strategies. Motivation problems associated with low-expectancy positively predicted regulation of achievement goals. Lack of value predicted the use of regulation situational interest, but not regulation of value. Experience of pressure is predicted by multiple strategies. Lastly, lack of urgency is not associated with any of the motivation regulation strategies. Such results may be explained by the possible role of motivation components (Miele & Scholer, 2018). The role of metamotivation remains unclear. Implications for theory and future research are discussed.